Effects of lead exposure on brain glucose metabolism and insulin signaling pathway in the hippocampus of rats. (August 2019) - Yun, Shaojun; Wu, Yanli; Niu, Ruiyan; Feng, Cuiping; Wang, Jundong
Highlights: Chronic Pb exposure could result in a lower weight gain in rats and a higher Pb content in the brain of model rats. Pb exposure reduced activities of key enzymes of glucose metabolism in the brain. Pb exposure could disrupt the insulin signaling pathway in the hippocampus of rats. Abstract: The aim of this study was to determine whether Pb affects glucose metabolism in the hippocampus of rats. Male Sprague-Dawley rats aged 21 days were orally administered a 0.1%, 0.2%, or 0.3% lead acetate solution in deionized water for 65 days. Then, the weight of the rats; brain Pb content; brain glucose levels; activities of hexokinase, fructose-6-phosphate kinase, pyruvate kinase, glucose-6-phosphate dehydrogenase; expression of genes related to the insulin signaling pathway; as well as the gene and protein expression of glucose transporter (GLUT)-1 and GLUT-3 in the hippocampus were evaluated. The results showed that Pb content in the brain tissue of rats in the dose groups significantly increased, whereas the body weight gain, activities of glucose metabolism-related enzymes, and expression of the insulin signaling pathway-related genes significantly decreased compared to the corresponding values in the control group. In comparison with the control group, the brain glucose levels increased significantly in the low-dose group, but there were no significant differences with the middle- and high-dose groups. Furthermore, the mRNA of GLUT-1 in the three dose groups and the GLUT-3 in the middle- and high-dose groups rose markedly, while the GLUT-1 and GLUT-3 protein expression significantly increased in the middle- and high-dose groups and in the high-dose group, respectively. Taken together, the results showed that Pb exposure resulted in a lower body weight gain, higher brain Pb content and also affected brain glucose metabolism and the insulin signaling pathway.